2020
DOI: 10.1021/acsnano.0c08622
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond the Debye Length: Overcoming Charge Screening Limitations in Next-Generation Bioelectronic Sensors

Abstract: Electronic biosensors are a natural fit for field-deployable diagnostic devices because they can be miniaturized, mass produced, and integrated with circuitry. Unfortunately, progress in the development of such platforms has been hindered by the fact that mobile ions present in biological samples screen charges from the target molecule, greatly reducing sensor sensitivity. Under physiological conditions, the thickness of the resulting electric double layer is less than 1 nm, and it has generally been assumed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 46 publications
0
99
0
Order By: Relevance
“…It has been shown that limiting the Debye volume at an electrode surface extends the EDL farther into the solution, thereby lessening the extent of electric field screening at that interface. [ 43 , 44 ] Consequently, the stronger electric fields within the nanopores increase the probability of a faradaic electron transfer event for a given conformation of an aptamer probe. Indeed, because of their high density of nanoscale features, nanoporous electrodes offer exactly the type of interface where screening is weaker and where we would predict faradaic electron transfer to be accelerated ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that limiting the Debye volume at an electrode surface extends the EDL farther into the solution, thereby lessening the extent of electric field screening at that interface. [ 43 , 44 ] Consequently, the stronger electric fields within the nanopores increase the probability of a faradaic electron transfer event for a given conformation of an aptamer probe. Indeed, because of their high density of nanoscale features, nanoporous electrodes offer exactly the type of interface where screening is weaker and where we would predict faradaic electron transfer to be accelerated ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in [ 41 ], the 10 mM PBS buffer was diluted to 0.01 mM, which increased the Debye length from 0.7 nm to 7 nm, comparable to the size of the positive-charged spike protein S1 subunit antibody (7–10 nm). However, dilution makes it difficult to detect low-abundance analytes [ 117 , 118 ].…”
Section: Latest Developed Biosensors For Covid-19mentioning
confidence: 99%
“…For instance, aptamer is useful to overcome the Debye-Hückel screening effect in eld-effect transistor (FET)-based biosensor (vide infra), which commonly hinder the electrical signal from the target molecules under high concentrations of such ions. 79 FET, integrated with proper biorecognition elements such as aptamer or antibody, is a unique and useful sensing device to detect biomolecular targets [80][81][82] offering many advantages such as real-time, highly sensitive, specic, and label-free transduction of biochemical signals. 83,84 In principle, the sensing mechanism of an FET device involves structural and functional integration of biorecognition element in which the selective interaction of bioreceptors and analyte produces changes in biophysical and biochemical signal.…”
Section: Biomarkers As Crucial Target For Biosensor Systemmentioning
confidence: 99%
“…Another vast obstacle of FET in clinical biosensing measurement relies on the high concentration of salts/buffers in clinical sample-induced Debye-Hückel screening effect. 79 Debye-Hückel effect is the discussion about the correlation of Debye length and unambiguous selective detection of macromolecules. Debye length (l D ) corresponds to the distance measured from FET-biosensor surface and electrolytic buffer solution (e.g., phosphate-buffered saline) describing the screening of surface charges by ions in an electrolyte solution.…”
Section: In Vitro Biosensing Systemmentioning
confidence: 99%